Characterizing ecoregions in Argentinian Patagonia using extant continental ostracods - Cusminsky, Gabriela Catalina (2020)
In order to characterize Patagonian (Argentina) ecoregions using non-marine ostracods, their associations in 69 environments were assessed. Twenty eight taxa were recorded, including 12 endemic of the Neotropical region. Our results indicate that Patagonian ostracods are mainly influenced by electrical conductivity (EC), altitude, pH, and temperature; and shows a correlation with Argentinian ecoregions. Assemblage I is composed of sites located at high altitude in the Andean Patagonian forest ecoregion. Host waters have low temperature, EC and pH, and support as representative species Cypris pubera, Eucypris virens, Bradleystrandesia fuscata, Tonacypris lutaria and Amphicypris nobilis. Assemblage II, related to mid-altitude environments in the Patagonian Steppe ecoregion, thrived in waters with moderate to high EC, and alkaline pH values. Dominant species includes Limnocythere rionegroensis, L. patagonica, E. virgata, Riocypris whatleyi, Riocypris sarsi, Newnhamia patagonica, Kapcypridopsis megapodus, Ilyocypris ramirezi and Penthesinelula incae. Assemblage III inhabited environments within Monte and Espinal ecoregions, situated in the eastern part of the study area at low altitude, EC moderate and temperate waters, supporting Heterocypris hyalinus, Amphicypris argentinensis, Sarscypridopsis aculeata, Cypridopsis vidua, Herpetocypris intermedia and Chlamidotheca incisa. Our results indicates that Argentinian Patagonia hosts a diverse ostracod fauna and highlights their capacity as proxies in ecological and palaeoenvironmental studies.